Journal Information and Editorial Board - Volume 6, Issue 1, 2021 - Idealogy Journal, ` (Idealogy Journal; Vol 6 No 1 (2021): Idealogy Journal (April 2021), 2021)
This section presented about the Journal Information, Editorial Board, Panel of Reviewer, Copyright Notice, and Committee of Publication Ethic. This information for further reference by the author for the official needs on their own career path. Keyword: Journal Information; Editorial Board; Panel of Reviewer; Copyright Notice; Committee of Publication Ethic